Community Empowerment Through Fresh Water Fish Cultivation Competence In Kabupaten Srono - Rozi, Muhamad Fahrur; Sunarti, Vevi; Husnul Hayati, Ridha; Petal Hia, Sentri (Universitas Negeri Padang, 2023)
This study aims to analyze the use of media literacy in freshwater fish farming in the Srono sub-district, Banyuwangi regency. This research was conducted in Srono District, Banyuwangi Regency using a quantitative approach to multiple linear regression analysis, then the data were analyzed descriptively. Collecting research data by distributing questionnaires prepared by researchers and has been tested for validity and reliability. The population in the study were 305 households that owned fish ponds. The research sample was taken using the disproportionate stratified random sampling technique, a sample of 75 respondents, the sample was drawn using the slovin formula. The results of this study are the utilization of community empowerment through freshwater fish cultivation competence in Kabupaten Srono starting from; instilling a sense of confidence and values in developing oneself, developing skills in the form of community expertise in cultivating fresh fish, maintain the emotional community in cultivating freshwater fish, forming individual social personalities in a prosperous society, developing self-motivation, developing community intellectual abilities, developing organizational culture in maintaining and nurturing members organization.